2005
DOI: 10.1186/1471-2334-5-18
|View full text |Cite
|
Sign up to set email alerts
|

A2 gene of Old World cutaneous Leishmania is a single highly conserved functional gene

Abstract: BackgroundLeishmaniases are among the most proteiform parasitic infections in humans ranging from unapparent to cutaneous, mucocutaneous or visceral diseases. The various clinical issues depend on complex and still poorly understood mechanisms where both host and parasite factors are interacting. Among the candidate factors of parasite virulence are the A2 genes, a family of multiple genes that are developmentally expressed in species of the Leishmania donovani group responsible for visceral diseases (VL). By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In these species, multiple copies of the A2 genes are arranged in tandem on Chr 22, whereas in L. major, the corresponding sequences have been found functionally expressed as a single copy gene (24). Amplification of these sequences in Li and Lm confirmed a full-length and truncated copy of the A2 gene(s), respectively, and revealed that each of the hybrids had inherited at least one A2 locus from each parent (Fig.…”
Section: Significancementioning
confidence: 99%
“…In these species, multiple copies of the A2 genes are arranged in tandem on Chr 22, whereas in L. major, the corresponding sequences have been found functionally expressed as a single copy gene (24). Amplification of these sequences in Li and Lm confirmed a full-length and truncated copy of the A2 gene(s), respectively, and revealed that each of the hybrids had inherited at least one A2 locus from each parent (Fig.…”
Section: Significancementioning
confidence: 99%
“…The A2 protein plays a role in promastigote-amastigote differentiation (Alcolea et al 2010) and is expressed solely during amastigote-stage host infection in L. donovani (Ghedin et al 1998;Zhang and Matlashewski 2001) but not L. major, and has been associated with the differing disease tropisms between the two species (Zhang et al 2003). In contrast to the conserved A2 locus in L. major (Garin et al 2005), functional CNVs have been previously observed in the L. donovani species complex, and we see significant sequence diversity and structural variation at this region even between our related lines. Whereas 39 and 59 A2-related genes possessed nine high-frequency protein-level SNPs, genes on the rest of that chromosome had only a total of four, suggesting a possible role for variability at this locus in A2 gene expression (Zhang et al 2003).…”
Section: )mentioning
confidence: 99%
“…For example, the amastigote stage specific A2 protein in CL isolates was lacking most of the nucleotide repeats that constitute the variable region at the 5′ end of the A2 sequences in VL that are responsible for its immunogenicity. 20 Further studies using a higher number of cutaneous disease patients and Leishmania species are needed to explore the lack of species-specific diagnosis in CL .…”
Section: Resultsmentioning
confidence: 99%